Tubular Injury Biomarkers to Detect Gentamicin-Induced Acute Kidney Injury in the Neonatal Intensive Care Unit - Jansen, Diana; Peters, Esther; Heemskerk, Suzanne; Koster-Kamphuis, Linda; Bouw, Martijn P.W.J.M.; Roelofs, Hennie M.J.; van Oeveren, Wim; van Heijst, Arno F.J.; Pickkers, Peter (American Journal of Perinatology, 2016)
Objective We evaluated whether urinary excretion of tubular injury markers could be useful for early detection of gentamicin (GM)-induced renal damage in neonates.Study Design We conducted a prospective, observational trial in neonates admitted to the neonatal intensive care unit (26 GM treated, 20 control). Kidney injury molecule-1 (KIM-1), neutrophil gelatinase–associated lipocalin (NGAL), N-acetyl-β-D-glucosaminidase (NAG), and π- and α-glutathione-S-transferase (GSTP1–1 and GSTA1–1) were measured every 2 hours during admission and compared with serum creatinine (sCr) and urine output.Results Nine neonates developed AKI during the course of the study. The peak in excretion of urinary biomarkers preceded the peak in sCr (p < 0.0001). GM administration resulted in a more pronounced increase of sCr compared with control (13 [12–28] vs. 10 µmol/L [8.5–17]; p < 0.05). The urinary excretion of NAG (178 [104–698] vs. 32 ng/mol Cr [9–82]; p < 0.001) and NGAL (569 [168–1,681] vs. 222 ng/mol Cr [90–497]; p < 0.05) was higher in the GM group compared with control and preceded the peak of sCr and urine output decrease.Conclusion GM administration to neonates is associated with renal damage reflected by a more pronounced increase in sCr preceded by urinary excretion of biomarkers. Urinary biomarkers may be useful for earlier identification of renal injury in neonates.
Keywords: urinary biomarkers; gentamicin; acute kidney injury; neonates